ANALISIS PENANGANAN REHABILITASI DAN REKONSTRUKSI PASCA GEMPA BUMI KABUPATEN CIANJUR - Leonardo Firmansyah, Risteruw; Bambang Nurcahya, Said; Mariany , Aria (LPPM Politeknik Pajajaran ICB, 2023)
As one of the countries that often faces natural disasters, Indonesia has created guidelines for handling rehabilitation and reconstruction after natural disasters. Various disasters, especially earthquakes, are natural disasters that take a lot of lives and material, so the author tries to analyze the handling of earthquake disasters that occur in the Regency. Cianjur in November 2022. This research method uses a qualitative approach with content analysis, namely conducting an analysis of reconstruction and rehabilitation after the earthquake disaster. Theories related to disasters have experienced a paradigm shift from pure science to applied science, although most of these disaster theories originate from practice and are then turned into theories. There is an interesting issue that arises, namely that disaster risk information provided by the government is not always accepted by the public. Some researchers offer through risk communication. However, the community also has its own information regarding disaster risks in their area. So it is not uncommon for people who believe in their beliefs and are attached to their region to not want to move from their region, even though it is declared by the government as an area that has a high level of risk for a particular disaster. Slow handling, especially during emergencies and after disasters, is caused by weak human resources. This can be overcome one way through good coordination and collaboration between stakeholders. Analysis of psychological, health and humanitarian rehabilitation as well as reconstruction of infrastructure, public facilities and settlements that have been carried out by the Cianjur Regency BPBD and the Cianjur Regency PUPR.